2017
DOI: 10.1007/s10753-017-0680-8
|View full text |Cite
|
Sign up to set email alerts
|

The Falconoid Luteolin Mitigates the Myocardial Inflammatory Response Induced by High-Carbohydrate/High-Fat Diet in Wistar Rats

Abstract: Luteolin is a major component of many medicinal plants and traditional medicines. The current study aims at testing its protective effect against high-carbohydrate/high-fat (HCHF) diet-induced cardiac dysfunction in rats. Male Wistar rats were divided into six groups as follows: control group that received standard rat chow, group received HCHF diet (~ 30% carbohydrate and 42% fat) daily for 16 weeks, and four groups received HCHF diet concurrently with luteolin (10, 25, 50 or 100 mg/kg; 10% w/v suspension in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
1
15
0
1
Order By: Relevance
“…For longer storage, it is hypothesized that ultra-low or low temperature storage may be better alternative approaches (29). A recent study demonstrated that luteolin mitigated the myocardial inflammatory response induced by a high-carbohydrate/high-fat diet, thus supporting the conclusion of the current study (49). Although there are several technical obstacles, such as irreversible injury during freezing, developments in cellular and molecular techniques may provide breakthroughs in long-term heart preservation in the near future.…”
Section: Discussionsupporting
confidence: 72%
“…For longer storage, it is hypothesized that ultra-low or low temperature storage may be better alternative approaches (29). A recent study demonstrated that luteolin mitigated the myocardial inflammatory response induced by a high-carbohydrate/high-fat diet, thus supporting the conclusion of the current study (49). Although there are several technical obstacles, such as irreversible injury during freezing, developments in cellular and molecular techniques may provide breakthroughs in long-term heart preservation in the near future.…”
Section: Discussionsupporting
confidence: 72%
“…High‐saturated‐fat and high‐sugar consumption has become more popular in most nations worldwide despite the accumulative evidence that it is associated with cardiometabolic dysfunction . Both a high‐saturated‐fat diet (HFD) and high‐saturated‐fat, high‐sugar diet (HFHS) have been used to induce cardiometabolic dysfunction in animals in order to investigate the mechanism responsible for their adverse effects on the peripheral metabolism and left‐ventricular (LV) function . A high‐fat diet can be divided into high‐unsaturated fat diet and high‐saturated fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the HFD consumption is associated with cardiac autonomic imbalance, an increased blood pressure, leading to LV dysfunction . Similar to the HFD, there are studies reported that HFHS also caused obese‐insulin resistance and LV dysfunction, but it did not affect blood pressure in rodents …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations